2017
DOI: 10.1287/mnsc.2015.2387
|View full text |Cite
|
Sign up to set email alerts
|

Past the Point of Speeding Up: The Negative Effects of Workload Saturation on Efficiency and Patient Severity

Abstract: Service organizations face a trade-off between high utilization and responsiveness. High utilization can improve financial performance, but causes congestion, which increases throughput time. Employees may manage this trade-off by reducing processing times during periods of high workload, resulting in an inverted U-shaped relationship between utilization and throughput time. Using two years of inpatient data from 203 California hospitals, we find evidence that patient length of stay (LOS) increases as occupanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(90 citation statements)
references
References 49 publications
4
86
0
Order By: Relevance
“…Since it can be difficult for hospitals to employ different types of physicians, contracting can potentially provide a mechanism to deal with patient needs (Loughry & Elms, 2006). In line with this, a more flexible supply of healthcare professionals has been shown to improve patient care as reflected in shorter length of stay (Berry Jaeker & Tucker, 2016).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Since it can be difficult for hospitals to employ different types of physicians, contracting can potentially provide a mechanism to deal with patient needs (Loughry & Elms, 2006). In line with this, a more flexible supply of healthcare professionals has been shown to improve patient care as reflected in shorter length of stay (Berry Jaeker & Tucker, 2016).…”
Section: Introductionmentioning
confidence: 86%
“…As the services literature highlights, process variation leads to inconsistent service quality (e.g., Frei, Kalakota, Leone, & Marx, 1999) and lower overall profitability (e.g., Heskett, Jones, Loveman, Sasser, & Schlesinger, 2008). Physicians must balance these standards with individualized care that meets patient needs (Berry Jaeker & Tucker, 2016). Physicians must balance these standards with individualized care that meets patient needs (Berry Jaeker & Tucker, 2016).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…During highly congested periods in hospitals, physicians often cut corners by discharging patients early, which results in a higher mortality rate (Kuntz et al, 2014). When congestion is extremely high, even if discharging a patient early is preferred, it is difficult for physicians to manage in practice (Berry Jaeker & Tucker, 2016). Moreover, trying to improve service quality by increasing available worker time can backfire because it may instead "induce service" that increases provider revenue without improving quality for customers (Debo et al, 2008).…”
Section: The Impact Of Available Processing Timementioning
confidence: 99%
“…This vector also includes control variables for the quarter-year (e.g., quarter 1 of 2010) of the visit to control for seasonality effects and time trends, based on clinical considerations (e.g., flu season), and in accordance with standard practice in the medical literature (e.g., Currie et al, 2016). Following prior research, we convert the daily census into an occupancy percentage (from 0 to 100%) by dividing the daily census by the maximum census in our study (Berry Jaeker & Tucker, 2016;Kuntz et al, 2014). We control for occupancy, which is the daily census of the hospital's ED in which patient i was treated, and include an occupancy-squared term because previous research has shown that occupancy can have nonlinear effects (KC & Terwiesch, 2012).…”
Section: Control Variablesmentioning
confidence: 99%
“…Using multiple settings within healthcare KC and Terwiesch (2009) show that service rates are endogenous to load. Multiple papers have built upon this finding: to replicate it in other contexts (Staats and Gino 2012), to show that quality may suffer due to load (Kuntz, Mennicken and Scholtes 2015), to show that workers may burn out due to load (Green, Savva and Savin 2012) and more generally show how load can alter behavior in an operating system (Tan and Netessine 2014;Berry Jaeker and Tucker 2015;Kim et al 2015). A key assumption in this line of work is that as individuals experience more load, they choose to work faster in the short-term, although this speeding up may negatively impact performance in the long-term.…”
Section: Introductionmentioning
confidence: 97%